Rapid and on-line instrumentation for food quality assurance (CRC, 2003)
Many measurements of product and process characteristics have traditionally been 'off-line', involving removing the product and taking it to a quality control laboratory for analysis over a period of hours or even days. However, the development of faster, more automated methods of production, and the shift to more proactive quality and safety management systems such as HACCP, has forced the food industry to look for more rapid methods with the potential for continuous, real-time measurement of products and processes. With its distinguished editor and international team of contributors, this important collection summarises key developments in this growing field. Part 1 reviews the emergence of new methods for analysing food safety. It includes chapters on the detection of foreign bodies, other contaminants such as toxins, pesticides, dioxins and veterinary residues, and rapid methods for detecting pathogenic and spoilage bacteria. Part 2 discusses the measurement of product quality. There are chapters on analysing ingredients such as additives and micronutrients, genetically-modified organisms and added water. A number of chapters discuss methods for analysing food composition, and the use of electronic noses to monitor food quality. A final chapter reviews ways of integrating such measurements into effective process control. Rapid and on-line instrumentation for food quality assurance provides a benchmark of good practice in this important field, and will be a valuable reference for the food industry.